Analisis Potensi Desa Wisata Pulesari Menuju Desa Wisata Halal Tahun 2020 - Yanma, Tareq Azis; Zaenuri, Muchammad (Jurnal Master Pariwisata (JUMPA), 2021)
Halal tourism village is an innovation in developing tourist village by prioritizing services for Muslim tourists. Halal tourism in Indonesia has only been developed in several regions, such as West Nusa Tenggara, Riau Islands, Aceh and West Sumatra. Pulesari tourism village is a tourism village in Sleman Regency which has halal tourism potential. Attractions that are shown mostly religious nuances. This study aims to analyze and identify the potential of Pulesari Tourism Village that can support the creation of a halal tourism village. This research is a descriptive qualitative research with a field to get data, make observations, documentations and interviews directly. Data analysis in this study combines the theory of tourism potential with several indicators from the Ministry of Tourism regarding halal tourism. The results of this study stated that Pulesari Tourism Village was not ready to be developed into a halal tourism village because several supporting facilities in the service of Muslim tourists had not yet been fulfilled. Keywords: Halal tourism village, Muslim tourists, Pulesari tourism village